Charge‐Transfer Salts Based on a Dissymmetrical Cyano‐Substituted Tetrathiafulvalene Donor. Issue 8 (16th February 2016) - Oliveira, Sandrina; Santos, Isabel C.; Lopes, Elsa B.; Coutinho, Joana T.; Pereira, Laura C. J.; Belo, Dulce; Rabaça, Sandra; Almeida, Manuel
Abstract: Three salts of the dissymmetrical TTF derivative cyanobenzene‐ethylenedithio‐tetrathiafulvalene (CNB‐EDT‐TTF) with different anions, namely, (CNB‐EDT‐TTF)2 [M(mnt)2 ] [M = Ni (1 ), Au (2 ); mnt = maleonitriledithiolate] and (CNB‐EDT‐TTF)FeBr4 (3 ) were prepared and characterized by single‐crystal X‐ray diffraction, magnetic susceptibility, and electrical conductivity measurements. Compounds1 and2 are isostructural with a crystal structure characterized by segregated chains of side‐by‐side donor dimers and acceptors, and compound3 presents donors in dimerized stacks. In spite of the different structural types and stoichiometries, all of these compounds have C–N··· H pairing interactions associated with R 2 2 (10) synthons between donors in nearby chains. All compounds are poor semiconductors, and the magnetic susceptibility of1 is dominated by the contribution of the paramagnetic [Ni(mnt)2 ] anions with small antiferromagnetic interactions. The magnetic susceptibility of3 is dominated by the paramagnetic FeBr4 anions and follows a Curie–Weiss law with a Weiss temperature θ = –19 K, which denotes significant antiferromagnetic interactions that are most likely mediated by the donors. Abstract : The salts (CNB‐EDT‐TTF)2 [M(mnt)2 ] (CNB‐EDT‐TTF = cyanobenzene‐ethylenedithio‐tetrathiafulvalene; mnt = maleonitriledithiolate; M = Ni, Au) and (CNB‐EDT‐TTF)FeBr4 with different structural types and stoichiometries present C–N··· H donor interactions that correspond to R 2 2 (10) synthons, and the donors do not have layered structures.